Microsoft Excel 2013 : building data models with PowerPivot - Ferrari, Alberto; Russo, Marco, 1967- (Sebastopol, CA : O'Reilly, 2013)
Transform your skills, data, and business - and create your own BI solutions using software you already know and love: Microsoft Excel. Two business intelligence (BI) experts take you inside PowerPivot functionality for Excel 2013, with a focus on real world scenarios, problem-solving, and data modeling.
Includes index.
oif 12/06/15
Loan
Keywords: Microsoft PowerPivot (Computer file); Microsoft Excel (Computer file); Data mining -- Computer programs